PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA KARYAWAN DAN KOMITMEN ORGANISASI PADA PT. KPM - Dewi, Kadek Sintha (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 7 Nomor 2 Tahun 2013)
The research objective was to determine the transformational leadership style influence on employees job satisfaction and organizational commitment on PT. KPM. The sample in this study was 30 people and data were processed using Partial Least square (PLS). The results showed significant effect of transformational leadership style on employee job satisfaction, employee  satisfaction significant influence on organizational commitment, and transformational leadership style indirect effect on organizational commitment. To foster employee  job  satisfaction  and  organizational  commitment,  the  company  needs  to  consider  the  needs  of employees as well as payment
Keywords: transformational leadership style, employee job satisfaction, organizational commitment